Optimization of Makespan in Job Shop Scheduling Problem by Golden Ball Algorithm - Fatima Sayoti; Mohammed Essaid Riffi; Halima Labani (Institute of Advanced Engineering and Science, 2016)
Job shop scheduling problem (JSSP) is considered to belong to the class of NP-hard combinatorial optimization problem. Finding a solution to this problem is equivalent to solving different problems of various fields such as industry and logistics. The objective of this work is to optimize the makespan in JSSP using Golden Ball algorithm. In this paper we propose an efficient adaptation of Golden Ball algorithm to the JSSP. Numerical results are presented for 36 instances of OR-Library. The computational results show that the proposed adaptation is competitive when compared with other existing methods in the literature; it can solve the most of the benchmark instances.